Risk factors for delayed diagnosis of endometrial cancer among black individuals: Results from the GUIDE-EC study - Maya E. Gross; Mindy Pike; Julianna Alson; Patrice Williams; Mollie E. Wood; Erica Marsh; Erin Carey; Til Stürmer; Ronit Katz; Whitney R. Robinson; Kemi M. Doll (Gynecologic Oncology Reports)
Objective: Black patients with endometrial cancer (EC) experience disproportionately advanced stage at diagnosis. We aimed to identify variables, beyond race and histologic subtype, which increase risk for delayed diagnosis of EC. Methods: This is a retrospective study of Black individuals with EC in a large academic-affiliated healthcare system from 2014 to 2020. Primary outcome was delayed diagnosis of EC, defined as prolonged time to diagnosis (>28 days to reach diagnosis). We used descriptive statistics, univariate regression, and factor analysis to identify variables associated with delayed diagnosis, achieve data reduction, and calculate odds ratios for delayed diagnosis. Results: Of 388 patients with EC included for analysis, one fifth (n = 79, 20 %) experienced delayed diagnosis. Ultrasound had the strongest association with delayed diagnosis in univariate regression (OR 4.4, 95 % CI 2.4, 7.8) and factor analysis (OR 2.2, 95 % CI 1.6, 3.0). BMI ≥ 40 (OR 1.9, 95 % CI 1.1, 3.3) was also associated with delayed diagnosis. Age ≥ 50 was associated with decreased odds of delayed diagnosis (OR 0.3, 95 % CI 0.2, 0.7). Presence of an endometrial biopsy was associated with decreased odds of delayed diagnosis on univariate regression (OR 0.4, 95 % CI 0.2, 1.4). Conclusions: A fifth of Black patients with EC experienced delayed diagnosis, and preoperative ultrasound was most strongly associated with delayed diagnosis. Providers should consider a tissue-sampling-first approach in Black patients at risk for EC.